2021
DOI: 10.3389/fnhum.2021.770107
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cortical-Striatal Network in Patients With Hemifacial Spasm

Abstract: Objective: Hemifacial spasm (HFS) is a kind of motor disorder, and the striatum plays a significant role in motor function. The purpose of this study was to explore the alterations of the cortical-striatal network in HFS using resting-state functional magnetic resonance imaging (fMRI).Methods: The fMRI data of 30 adult patients with primary unilateral HFS (15 left-side and 15 right-side) and 30 healthy controls were collected. Six subregions of the striatum in each hemisphere were selected for functional conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Categorical variables were analyzed using the chi-square test. Pearson correlation analysis was used to evaluate the correlation between changes in topological properties and clinical scale scores (Gao et al, 2021;Wang et al, 2022). The False Discovery Rate (FDR) method was used to correct P-values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Categorical variables were analyzed using the chi-square test. Pearson correlation analysis was used to evaluate the correlation between changes in topological properties and clinical scale scores (Gao et al, 2021;Wang et al, 2022). The False Discovery Rate (FDR) method was used to correct P-values.…”
Section: Discussionmentioning
confidence: 99%
“…To unify the affected side of the patients, the T1WI and DTI data with right HFS (11 cases) were ipped from right to left prior to preprocessing (Song et al, 2017;Gao et al, 2021). All DTI data were analyzed using the PANDA toolbox (Pipeline for Analyzing Brain Diffusion Images toolkit, https://www.nitrc.org/projects/panda/) (Cui et al, 2013;Lin et al, 2022).…”
Section: Dti Preprocessingmentioning
confidence: 99%
“…Prior rs-fMRI studies associated with HFS provided evidence that there was not only hyperexcitability in the facial nucleus and the brain areas involved in facial movement, but also abnormality in the areas related to inhibitory motor control. The abnormal functional connectivity (FC) between the thalamus, striatum, and motor cortex was also found in patients with HFS 11,15–17. In addition, another study suggested abnormal FC between the amygdala and the brain areas related to visual stimuli coordination and emotion generation or regulation 7.…”
mentioning
confidence: 99%
“…The abnormal functional connectivity (FC) between the thalamus, striatum, and motor cortex was also found in patients with HFS. 11,[15][16][17] In addition, another study suggested abnormal FC between the amygdala and the brain areas related to visual stimuli coordination and emotion generation or regulation. 7 In short, the alterations of gray matter structure and spontaneous activities in HFS patients are mainly concentrated in several areas, which are mostly involved in facial movement and motor control, emotion regulation, and visual processing.…”
mentioning
confidence: 99%